Age-Specific Clinical and Laboratory Features and Renal Involvement in Children with MIS-C: A Single Tertiary Centre Experience from Vojvodina - Borko Milanović; Vesna Stojanović; Gordana Vijatov-Ðurić; Marijana Savin; Andrea Ðuretić; Jelena Kesić; Nenad Barišić; Ognjen Ležakov; Ivana Vorgučin; Gordana Vilotijević-Dautović; Katarina Koprivšek (Medicina)
Backgrounds and Objectives: Multisystem Inflammatory Syndrome in Children (MIS-C) is a rare but potentially severe complication of SARS-CoV-2 infection, with increasingly reported renal manifestations. Materials and Methods: The aim of this retrospective study was to compare clinical and laboratory characteristics across age categories, with special emphasis on renal function. We analysed data from 64 patients with MIS-C treated between July 2020 and December 2023. Results: In children under 3 years of age, there was a higher prevalence of leucocytosis, elevated platelet counts, and anaemia, along with a lower frequency of complications. The 3–6-year age group was characterized by the presence of rash, hypoalbuminemia, and elevated transaminases. The 7–12-year age group showed the highest rate of organ dysfunction. In adolescents (13–18 years), neurological symptoms, the highest BMI values, the greatest prevalence of comorbidities, leukopenia, lymphopenia, and elevated GGT levels were observed. The incidence of acute kidney injury (AKI) was 6.3% (n = 4/64). Following treatment, the majority of patients achieved full recovery (n = 61/64; 95.2%). Conclusions: There are pronounced age-related differences in the clinical presentation of MIS-C, with distinct immune and clinical patterns suggesting developmental influences on disease expression and outcomes. Older children showed a higher prevalence of comorbidities and organ dysfunction compared to younger patients. Notably, this study found a markedly lower incidence of acute kidney injury (6.3%) compared to previously reported rates (20–30%), indicating potential regional or age-related protective factors. These findings highlight the importance of age-specific evaluation in MIS-C and underscore the need for further multicentre research to refine therapeutic protocols.